Factors affecting the price of housing in Malaysia / Muhammad Adham Musa - Musa, Muhammad Adham (Faculty of Business and Management, 2015)
This research focuses on the determinants of Malaysian housing market price. According to (Jarad, 2010)Malaysia has obtained so many benefit by become a developing country through a development of housing industry. Even various construction and restriction, the Malaysian housing development has continued fight (Agus, 1997). The economic growth process in local and international is influence by construction activities (Field, 1988) even at the past construction is only focus on the agriculture and manufacturing sectors. However, (Tiwari, 2001) stated that economic of country can strengthen where the residential housing construction contributes significantly to overall production activities. The construction industry has to aware as simply providing infrastructure and solutions to problem of shelters and determination in the changing process (Field, 1988). Malaysia offers the lowest average price per square feet for house if compared directly with Asian Neighboring countries, aside from Indonesia. The Government of Malaysia recognizes that housing is a basic need for every citizen. It is also an important component of the urban economy. Therefore, housing developments in Malaysia are carried out by both parties, the public sector and the private sector, in terms of low, medium, and high-cost houses.